2016
DOI: 10.1038/srep28505
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Effects against S. aureus and Physicochemical Properties of Plasma Activated Water stored at different temperatures

Abstract: Water activated by non-thermal plasma creates an acidified solution containing reactive oxygen and nitrogen species, known as plasma-activated water (PAW). The objective of this study was to investigate the effects of different storage temperatures (25 °C, 4 °C, −20 °C, −80 °C) on bactericidal activities against S. aureus and physicochemical properties of PAW up to 30 days. Interestingly, PAW stored at −80 °C yielded the best antibacterial activity against Staphylococcus aureus, 3~4 log reduction over a 30-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
222
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(267 citation statements)
references
References 46 publications
(63 reference statements)
15
222
0
Order By: Relevance
“…Thus, the synergistic effects of acid pH and ROS and RNS are a guarantee of a good germicidal action of PAW. These findings are consistent with Traylor et al ., and Shen et al ., who showed that the action of DBD air PAW on S. aureus and Escherichia coli bacteria, respectively, was effective only at acidic pHs.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the synergistic effects of acid pH and ROS and RNS are a guarantee of a good germicidal action of PAW. These findings are consistent with Traylor et al ., and Shen et al ., who showed that the action of DBD air PAW on S. aureus and Escherichia coli bacteria, respectively, was effective only at acidic pHs.…”
Section: Resultssupporting
confidence: 92%
“…The nitrite, nitrate and peroxide contents obtained were therefore at this pH. Previous works on activated water generated by other types of discharge also have proved the formation of these species, even if the contents varied from one study to the other, depending on the duration of the discharge and the plasma gas.…”
Section: Resultssupporting
confidence: 62%
“…In‐water application of plasma using air as a carrier gas produced both atomic oxygen and atomic nitrogen species in the activated water. Atomic oxygen species, in turn, produced O 3 , OH, and H 2 O 2 , whereas the atomic nitrogen formed nitrites, nitrates, S‐nitrosothiols, and nitrosamines in PAW (Shen et al., ). Further, the emission intensity of plasma and ORP of treated water is greater when the plasma is produced inside the water when compared to above‐water treatment (Tian et al., ).…”
Section: Ntp–liquid Interactionsmentioning
confidence: 99%
“…Shen et al. () called PAW as a “green disinfectant” because it has a less adverse impact on the environment than chemical agents and proposed it as a promising food sanitizer.…”
Section: Introductionmentioning
confidence: 99%
“…phase are also decided by the storage temperature (Shen, et al, 2016). Therefore, 252 appropriate temperature of storage should be ensured as a hurdle to prevent recovery of 253 cell activity.…”
mentioning
confidence: 99%